The Effectiveness of Using Games on Primary Stage Students for the Achievement of English Language skills. - Sandamali, K P S (IJARIIE, 2020)
English Language Teaching is a vital fact in the modern society. Sri Lankan Education system has given full attention to develop English Language skills among the students of the country. It has greatly identified that the teachers need to deploy appropriate teaching method with the level and the need of the students to master the language. This study found that using games for language teaching in primary students in the schools has greatly benefited. The selected was ideally matched with the deployed method. It was found positive to use games with beginners where it is appropriate.
Keywords: English Language Teaching; Teaching method